Future geographical distribution of Aedes albopictus in China under climate change scenarios. - Jianjun Xu; Rulin Wang; Zhenhan Mo; Han Zhang; Yujing Zhang (PLoS ONE)
Amidst the escalating global threat of dengue fever, the distribution of its primary vector, Aedes albopictus, is undergoing significant shifts due to climate change. This study utilized Biomod2 to simulate the distribution changes of Ae. albopictus in China under future climate scenarios, providing critical insights for public health preparedness. Results showed that, the ensemble model achieved an ROC value of 0.968, a TSS value of 0.81, and a KAPPA value of 0.789, indicating high accuracy. Under current climate condition, the highly suitability regions were predominantly in the southern and eastern coastal areas of China. Guangdong, Guangxi, and Hunan possessed the largest areas of highly suitability, measuring 15.61 × 104 km2, 20.84 × 104 km2 and 11.71 × 104 km2, respectively. Under SSP1-2.6 in the 2050s, highly suitability regions were projected to expand significantly, particularly in central Guangxi, northern Guangdong, and central Fujian. Centroids of the total suitability regions were predicted to shift southeast under SSP1-2.6 and SSP5-8.5, and northeast under SSP2-4.5 and SSP3-7.0, reflecting the dynamic response of Ae. albopictus to climate change. These findings underscore the imperative for climate-adaptive strategies in public health policies to mitigate the risks of dengue fever transmission in China.